Acetazolamide fails to decrease pulmonary artery pressure at high altitude in partially acclimatized humans - Basnyat, B.; Hargrove, J.; Holck, P. S.; Srivastav, S.; Alekh, K.; Ghimire, L. M.; Pandey, K.; Griffiths, A.; Shankar, R.; Kaul, K.; Paudyal, A.; Stasiuk, D.; et al. (High Altitude Medicine & Biology, 2008)
In this randomized, double-blind placebo controlled trial our objectives were to determine if acetazolamide is capable of preventing high altitude pulmonary edema (HAPE) in trekkers traveling between 4250 m (Pheriche)\4350 m (Dingboche) and 5000 m (Lobuje) in Nepal; to determine if acetazolamide decreases pulmonary artery systolic pressures (PASP) at high altitude; and to determine if there is an association with PASP and signs and symptoms of HAPE. Participants received either acetazolamide 250 mg PO BID or placebo at Pheriche\Dingboche and were reassessed in Lobuje. The Lake Louise Consensus Criteria were used for the diagnosis of HAPE, and cardiac ultrasonography was used to measure the velocity of tricuspid regurgitation and estimate PASP. Complete measurements were performed on 339 of the 364 subjects (164 in the placebo group, 175 in the acetazolamide group). No cases of HAPE were observed in either study group nor were differences in the signs and symptoms of HAPE found between the two groups. Mean PASP values did not differ significantly between the acetazolamide and placebo groups (31.3 and 32.6 mmHg, respectively). An increasing number of signs and symptoms of HAPE was associated with elevated PASP (p < 0.01). The efficacy of acetazolamide against acute mountain sickness, however, was significant with a 21.9% incidence in the placebo group compared to 10.2 % in the acetazolamide group (p < 0.01). Given the lack of cases of HAPE in either group, we can draw no conclusions about the efficacy of acetazolamide in preventing HAPE, but the absence of effect on PASP suggests that any effect may be minor possibly owing to partial acclimatization during the trek up to 4200 m.